Targeting MK2 Is a Novel Approach to Interfere in Multiple Myeloma - Guo, Mengjie; Sun, Dongdong; Fan, Zhimin; Yuan, Yuxia; Shao, Miaomiao; Hou, Jianhao; Zhu, Yuqi; Wei, Rongfang; Zhu, Yan; Qian, Jinjun; Li, Fei; Yang, Ye; et al. (Frontiers in Oncology, 2019)
MAPKAPK2 (MK2), the direct substrate of p38 MAPK, has been well acknowledged as an attractive drug target for cancer therapy. However, few studies have assessed the functions of it in multiple myeloma (MM). In the present study, MK2 expression of MM patients was analyzed by gene expression profiling (GEP) and array-based comparative genomic hybridization (aCGH). Several experiments in vitro including MTT assay, Western blot and flow cytometry analysis were performed to identify the function of MK2 in MM. In addition, we conducted mouse survival experiments to explain the effects of MK2 on MM in vivo. mRNA level of MK2 and chromosomal gain of MK2 locus in MM cells significantly increased compared to normal samples. Furthermore, MM patients with high expression of MK2 were associated with poor outcome. Follow-up studies showed that MK2 exerted remarkably positive effect on MM cell proliferation and drug-resistance. Further exploration focusing on MK2 inhibitor Ⅳ revealed its inhibitory action on MM growth and drug-resistance, as well as improving survival in mouse model. In addition, combination of MK2 inhibitor Ⅳ and the key MM therapeutic agents including bortezomib, doxorubicin or dexamethasone facilitated curative effects on inhibiting MM cell proliferation. Taken together, our study reveals the clinical relevance of MK2 inhibition in MM and demonstrates that targeting MK2 may afford a new therapeutic approach to MM.